1999
DOI: 10.1128/jvi.73.1.618-630.1999
|View full text |Cite
|
Sign up to set email alerts
|

Limited Breadth of the Protective Immunity Elicited by Simian Immunodeficiency Virus SIVmne gp160 Vaccines in a Combination Immunization Regimen

Abstract: We previously reported that immunization with recombinant simian immunodeficiency virus SIVmne envelope (gp160) vaccines protected macaques against an intravenous challenge by the cloned homologous virus, E11S. In this study, we confirmed this observation and found that the vaccines were effective not only against virus grown on human T-cell lines but also against virus grown on macaque peripheral blood mononuclear cells (PBMC). The breadth of protection, however, was limited. In three experiments, 3 of 10 ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 56 publications
3
22
3
Order By: Relevance
“…Our observation that CL8 vaccines protected against homologous CL8 challenge is consistent with our previous findings [13,[31][32][33], although different challenge viruses and animal species were used (molecular clone and pig-tailed macaques in the current study vs. biological clone E11S and cynomolgus macaques in previous ones). Also in line with our previous observation [31,32] is the finding that CL8 vaccines failed to protect against a highly virulent virus 170. However, protective efficacy of the CL8 vaccines was not restricted to the minimally pathogenic homologous virus, as protection and substantial reduction of viral load was achieved in CL8-immunized macaques challenged by the 170/8 chimera, infection by which resulted in high and persistent viremia accompanied by progressive and irreversible CD4 + T cells loss.…”
Section: Vaccines From Temporal Isolates Of Sivmnesupporting
confidence: 92%
“…Our observation that CL8 vaccines protected against homologous CL8 challenge is consistent with our previous findings [13,[31][32][33], although different challenge viruses and animal species were used (molecular clone and pig-tailed macaques in the current study vs. biological clone E11S and cynomolgus macaques in previous ones). Also in line with our previous observation [31,32] is the finding that CL8 vaccines failed to protect against a highly virulent virus 170. However, protective efficacy of the CL8 vaccines was not restricted to the minimally pathogenic homologous virus, as protection and substantial reduction of viral load was achieved in CL8-immunized macaques challenged by the 170/8 chimera, infection by which resulted in high and persistent viremia accompanied by progressive and irreversible CD4 + T cells loss.…”
Section: Vaccines From Temporal Isolates Of Sivmnesupporting
confidence: 92%
“…Occult or silent infection, characterized by an undetectable antibody response and the ability to isolate or amplify virus from PBMC obtained at only a few time points, has also been reported after experimental simian immunodeficiency virus (SIV) challenge, a model commonly used for studying HIV-1 transmission and pathogenesis. Such infections occur following inoculation of non-human primates with low doses of virus, and are more frequently associated with mucosal (intravaginal, intrarectal or oral) (Miller et al, 1994;Pauza et al, 1993;Trivedi et al, 1996;Van Rompay et al, 1998) than intravenous routes of challenge (Petry et al, 1997;Polacino et al, 1999). Similar to findings in HIV-1 infection, virus-specific T cell immunity, such as proliferation and IFN-γ responses, has been detected (Ma et al, 2004;McChesney et al, 1998;McDermott et al, 2004;Murphey-Corb et al, 1999;Petry et al, 1997).…”
Section: Introductionmentioning
confidence: 81%
“…111,112 A vaccine protocol involving priming with SIV-env gene in vaccinia and a boost with Env protein protected completely against SIV infection; however, the protection was only for a homologous viral challenge-a fact that underscores the importance of using epitopes that are shared by most strains. 113 A different protocol with Gag-pol genes in a modified vaccinia virus showed that the induction of cytotoxic Tcell Gag epitopes correlated with SIV viremia reduction, similar to the association of CD8 + T cells and disease progression found in human beings. 50,114 To date, few HIV vaccines have been tested in phase I trials and demonstrated to be safe, though only modest levels of HIV-specific CD4 + and CD8 + T-cell responses have been elicited.…”
Section: Vaccine Developmentmentioning
confidence: 57%